Online prevention programmes for university students: stakeholder perspectives from six European countries. (7th July 2021) - Irish, Madeleine; Kuso, Stefanie; Simek, Monika; Zeiler, Michael; Potterton, Rachel; Musiat, Peter; Nitsch, Martina; Wagner, Gudrun; Karwautz, Andreas; Bolinski, Felix; Karyotaki, Eirini; Rovira, Carla Soler; et al.
Abstract: Background: Students beginning university are at a heightened risk for developing mental health disorders. Online prevention and early intervention programmes targeting mental health have the potential to reduce this risk, however, previous research has shown uptake to be rather poor. Understanding university stakeholders' (e.g. governing level and delivery staff [DS] and students) views and attitudes towards such online prevention programmes could help with their development, implementation and dissemination within university settings. Methods: Semi-structured interviews, focus groups and online surveys were completed with staff at a governing level, university students and DS (i.e. student health or teaching staff) from six European countries. They were asked about their experiences with, and needs and attitudes towards, online prevention programmes, as well as the factors that influence the translation of these programmes into real-world settings. Results were analyzed using thematic analysis. Results: Participating stakeholders knew little about online prevention programmes for university settings; however, they viewed them as acceptable. The main themes to emerge were the basic conditions and content of the programmes, the awareness and engagement, the resources needed, the usability and the responsibility and ongoing efforts to increase reach. Conclusions: Overall, although these stakeholders had little knowledge about online prevention programmes, they were open to the idea of introducing them. They could see the potential benefits that these programmes might bring to a university setting as a whole and the individual students and staff members.